Papillary carcinoma arising in a thyroglossal duct cyst: A case report - Desalegn Fekadu; Bereket Girum; Gemechis Asefa; Abdi Alemayehu; Michael Tekelhaimanot (Journal of Clinical and Translational Endocrinology Case Reports, 2024)
Thyroglossal duct cysts are one of the most common causes of anterior neck swelling. Thyroglossal duct carcinoma arising from these cysts is quite rare; it occurs in less than 1 % of all the thyroglossal duct cysts. Imaging plays a crucial role in evaluating these lesions and suggesting further pathologic workup in suspicious cases. We report a case of a 30-year-old woman with a diagnosis of papillary carcinoma within the thyroglossal duct cyst.